The Conservation of the Art of Exile in Museums: From its Constitution to the Problems for its Enhancement - Real López, Inmaculada (Eikón / Imago, 2019)
The museum initiatives for the conservation of the legacies of the diaspora have evolved over the last decades. Not all projects have been viable, some made them feasible, others were left in the utopia of an idea. Being a politically committed art, we must take into account the factors that have influenced the conservation of this heritage made during the Spanish Republican exile. In this article it is proposed to study which have been the main modalities of museums launched, the difficulties encountered, as well as their evolution process.